2017
DOI: 10.1007/s11682-017-9680-4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of regional homogeneity and white matter hyperintensities in amnestic mild cognitive impairment subtypes are related to cognition and CSF biomarkers

Abstract: Amnestic mild cognitive impairment can be further classified as single-domain aMCI (SD-aMCI) with isolated memory deficit, or multi-domain aMCI (MD-aMCI) if memory deficit is combined with impairment in other cognitive domains. Prior studies reported these clinical subtypes presumably differ in etiology. Thus, we aimed to explore the possible mechanisms between different aMCI subtypes by assessing alteration in brain activity and brain vasculature, and their relations with CSF AD biomarkers. 49 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The first important finding is higher fALFF in the left-sided superior-to-middle frontal gyri and middle-to-inferior temporal gyri in the sd-aMCI than both the md-aMCI and HC groups. The superior and middle frontal gyri are involved in a series of cognitive processes, such as executive function and working memory (Kim et al, 2014;Zamora et al, 2016), while the lateral temporal cortex is more involved in episodic memory (Luo et al, 2018). These cognitive functions are typically impaired in AD and MCI patients (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The first important finding is higher fALFF in the left-sided superior-to-middle frontal gyri and middle-to-inferior temporal gyri in the sd-aMCI than both the md-aMCI and HC groups. The superior and middle frontal gyri are involved in a series of cognitive processes, such as executive function and working memory (Kim et al, 2014;Zamora et al, 2016), while the lateral temporal cortex is more involved in episodic memory (Luo et al, 2018). These cognitive functions are typically impaired in AD and MCI patients (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, only the MD-aMCI simultaneously displayed inter-hemispheric functional connectivity decrease in MTG, supporting the notion that the MD-aMCI is a more advanced disease form than the SD-aMCI. Notably, one study pointed out that SD-aMCI displayed decreased regional activity in right MTG relative to NC ( Luo et al, 2018a ). Accordingly, we speculated that the intact inter-hemispheric connectivity in SD-aMCI might compensate its unilateral MTL impairment to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…However, as MCI is a heterogeneous state, AD biomarker related approaches and detailed cognitive examinations may bear more fruit. A recent study combing rs-fMRI and CSF showed the ReHo value was associated with A β level in superior temporal gyrus in single domain MCI while the multiple-domain MCI exhibited a more complex pattern of pathology and functional activity (47).…”
Section: Mild Cognitive Impairmentmentioning
confidence: 99%